2008
DOI: 10.1002/polb.21423
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of multiple melting behavior of spherulites comprising ring‐band shell/ringless core in polymorphic poly(butylene adipate)

Abstract: In‐depth interpretation of ring‐banded spherulitic morphology, crystals, polymorphism, and complex melting behavior in poly(1,4‐butylene adipate) (PBA) were analyzed via a procedure of designing composite core‐shell spherulites, in which two lamellar patterns (ring‐band vs. ringless) were packed by subjecting to crystallization at two‐step temperature schemes with specific temperatures and times. By heating to 52 °C and holding at that temperature for 30 min annealing, the core can be stripped off by melting, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…Some semicrystalline polymers or polymer blends have been reported to form ring‐banded spherulites at specific crystallization conditions . However, the formation of ring‐banded spherulite morphology remains one of the most challenging and complex issues in the field of crystalline polymer morphology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some semicrystalline polymers or polymer blends have been reported to form ring‐banded spherulites at specific crystallization conditions . However, the formation of ring‐banded spherulite morphology remains one of the most challenging and complex issues in the field of crystalline polymer morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Ring‐banded spherulites can be found in many polymers of various structures. Polyesters are among the most studied polymers that show ring‐banded spherulites upon melt crystallization; in addition, poly(vinylidene fluoride) (PVDF) (at T c = 168 °C), blends of liquid‐crystalline poly(aryl ether ketone) (LC‐PAEK), and poly(ether ether ketone) (PEEK) (by dynamically cooling from 380 °C to ambient termperature), or block copolymers such as poly(ε‐caprolactone‐ block ‐ethylene oxide) have also been shown to exhibit ring‐banded spherulites. Different from the conventional ring‐banded spherulites whose formation mechanism has been approached from a lamellar twisting model, the periodical growth/precipitation‐induced concentric banded spherulites, usually non‐birefringent in alternating rings, are derived from a diffusion process along the radial direction.…”
Section: Introductionmentioning
confidence: 99%
“…To utilize the free‐surface nature of AFM in dealing with the difficulty and complexity in the subject of ring‐banded crystals in polymers, even more innovative procedures are needed. Earlier studies have demonstrated the feasibility of compacting two‐ or three‐alternating layered spherulites in semicrystalline poly(1,4‐butylene adipate) (PBA)14 by subjecting it to stepwise crystallization. The sequence and number of layers in thin‐film confined spherulites can be designed by alternating steps of isothermal crystallization temperature with proper holding time.…”
Section: Introductionmentioning
confidence: 99%
“…Alternating ring‐banded/ring‐less layers can be packed into a single spherulite by crystallization under stepwise temperature schemes. PBA is quite unusual in that it is known to possess polymorphic crystal cells and is capable of developing ring‐band or regular Maltese‐cross spherulites in two proximate temperature regimes,14 while at yet higher temperatures, a morphology of straight hexagonal lamellae replaces the round‐shaped spherulites 15. The spherulite that consists of two patterns in a single spherulite could then be used for convenient in situ AFM characterization for close comparison and analyses of lamellae in ring‐banded versus ring‐less crystals.…”
Section: Introductionmentioning
confidence: 99%
“…A series of methods are adopted to control the polymorphic behavior of PBA . First, modulation of crystallization temperature provides an effective way to control the crystal form of PBA . The α‐form PBA is generally formed during isothermal crystallization at high temperatures (eg, above 33°C).…”
Section: Introductionmentioning
confidence: 99%